Bicarbonate loading and performance enhancement in half mile sprinting - Rodbell, B. L.; Shepherd, T.; Taylor, W.; Marley, W. P. (Medicine & Science in Sports & Exercise, 1998)
The effects of bicarbonate loading on 800- running times were investigated. NaHCO3 and placebo tablet and no-tablet conditions were compared. Dose size was 300 mg/kgbw and ingestion occurred one-hour before and immediately following each trial. There were no differences in run times or post-run measures. Implication. Bicarbonate loading does not assist 800-m running.